High amylase resistant starch to decrease stool output in people with short bowel syndrome: A pilot trial. (February 2019) - Hamilton, Kate; Crowe, Tim; Testro, Adam
Summary: Short bowel syndrome (SBS) is defined as having less than 200 cm of functional small bowel. Malabsorptive diarrhoea and dehydration are difficult to manage despite medical therapy and dietary manipulations. Evidence shows that supplementing the diet with High Amylase Resistant Starch (HARS) can reduce diarrhoea from a number of causes including gastroenteritis. It is hypothesised HARS will decrease stool output via the production of short chain fatty acids and the resultant increased water reabsorption. This study aimed to determine if the addition of HARS can reduce diarrhoea in patients with SBS. Methods: Patients with SBS with colon in continuity were recruited from the intestinal rehabilitation clinic at Austin Health. The study was a 2 week crossover trial. Each participant completed the control and the intervention (addition of 50 g HARS to usual diet). Total daily stool weight and number of bowel actions per day were compared between groups using paired t -tests. Results: Eight adults (58% male, mean age 55.7 yrs) were recruited. Five participants completed the trial. Total daily stool weight was reduced in all participants when consuming HARS. Mean daily stool output was significantly decreased 1049 ± 519 g/d to 804 ± 585 g/d (p = 0.023). Number of bowel actions per day showed a trend to reduction. Conclusion: This study gives some support to the hypothesis that the addition of HARS into the diet of patients with short bowel syndrome reduces stool output. Longer trials are required to confirm the effect on nutritional/hydration status.